2011
DOI: 10.1155/2011/107497
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic, Rural-Urban, and Racial Inequalities in US Cancer Mortality: Part I—All Cancers and Lung Cancer and Part II—Colorectal, Prostate, Breast, and Cervical Cancers

Abstract: We analyzed socioeconomic, rural-urban, and racial inequalities in US mortality from all cancers, lung, colorectal, prostate, breast, and cervical cancers. A deprivation index and rural-urban continuum were linked to the 2003–2007 county-level mortality data. Mortality rates and risk ratios were calculated for each socioeconomic, rural-urban, and racial group. Weighted linear regression yielded relative impacts of deprivation and rural-urban residence. Those in more deprived groups and rural areas had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
360
2
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(386 citation statements)
references
References 55 publications
19
360
2
5
Order By: Relevance
“…Si bien se ha estudiado la etiología del cáncer de mama a nivel individual, aún es necesario abordar cuáles son las causas de la enfermedad a nivel poblacional, que no necesariamente serán las mismas y el análisis ecológico contribuye a dilucidar esta pregunta 36 . Las asociaciones encontradas han sido descritas en la literatura internacional, esto es, la relación del cáncer de mama con el grado de urbanización y con mayor educación 4,37 . Esto podría explicarse por la mayor prevalencia de factores de riesgo de tipo hormonal en mujeres residentes en comunas urbanas y por diferencias en las etapas de la transición epidemiológica a lo largo del país.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Si bien se ha estudiado la etiología del cáncer de mama a nivel individual, aún es necesario abordar cuáles son las causas de la enfermedad a nivel poblacional, que no necesariamente serán las mismas y el análisis ecológico contribuye a dilucidar esta pregunta 36 . Las asociaciones encontradas han sido descritas en la literatura internacional, esto es, la relación del cáncer de mama con el grado de urbanización y con mayor educación 4,37 . Esto podría explicarse por la mayor prevalencia de factores de riesgo de tipo hormonal en mujeres residentes en comunas urbanas y por diferencias en las etapas de la transición epidemiológica a lo largo del país.…”
Section: Discussionunclassified
“…Esto podría explicarse por la mayor prevalencia de factores de riesgo de tipo hormonal en mujeres residentes en comunas urbanas y por diferencias en las etapas de la transición epidemiológica a lo largo del país. No obstante, en países desarrollados este mayor riesgo en áreas urbanas se ha trasladado al sector rural, debido a factores relacionados con la detección y acceso a tratamiento oportuno 37 .…”
Section: Discussionunclassified
“…Du et al (2011);White et al (2011);Taksler, Keating, and Cutler (2012);and Singh, Williams, Siahpush, and Mulhollen (2011) have all reported shorter survival in African American men after the diagnosis of PC. In these studies, the racial gap in survival remained after adjusting for known predictors of cancer survival.…”
Section: Discussionmentioning
confidence: 99%
“…39 CRC mortality across the United States is associated with neighborhood-level socioeconomic deprivation. 40 In Texas, late detection of cancer was associated with the Well-Being Index of socioeconomic deprivation, as well as lack of health insurance, physician shortage, and Hispanic ethnicity. 41 In a national study, individuals with the least education were found to have significantly higher CRC death rates for each racial ethnic group in virtually all states.…”
Section: Socioeconomic Factors As Drivers Of County-level Variation Imentioning
confidence: 99%